Cannabis and the Undercommons of Care: Producing Fugitive Value in Punitive Los Angeles - Chlala, Robert (ACME, 2025)
In the last two decades, shuttered warehouse-manufacturing sites and emptied retail across Los Angeles/Tovaangar were repurposed into the largest medical cannabis dispensary and indoor cultivation economy in the US. Drawing from more than twelve years of ethnographic participation, this paper bridges Black radical theory, disability studies and Buddhist humanist geographic perspectives to understand how cannabis workers, owner-operators, and patients produced fugitive forms of value. These forms of care, collective relationships, and material benefit challenge racial capitalist accumulation and offer distinct, even if fleeting moments of freedom. Facing death-dealing violence, marginalized communities created places of care at the “outlaw edge” that housed an undercommons of health practices and knowledge that include pleasure and non-hierarchical solidarities. These created respite and relief from interrelated geographies of abandonment, broken windows urban governance, and dispossession defining early 21st Century LA. Exploring cannabis economies offers a means to reconceptualize criminalization as a singular relation to carcerality, and to deepen our understanding of law, capitalism, and the forms of value generation being targeted. Ultimately, legalization in this context poses critical conundrums for participants in fugitive economies on what is gained and lost in further assimilation into racial capitalist urban economies. In other words, cannabis begs the question: can freedom only be found in flight?